Dense 1, 2, 4, 5-tetramethylimidazolium-functionlized anion exchange membranes based on poly(aryl ether sulfone)s with high alkaline stability for water electrolysis. (12th March 2023) - Qian, Jiafeng; Wang, Chenyi; Zhang, Xiaojing; Zhao, Xiaoyan; Li, Jian; Ren, Qiang
Abstract: Anion exchange membranes with enough alkaline stability and ionic conductivity are essential for water electrolysis. In this work, a class of anion exchange membranes (PAES-TMI-x) with dense 1, 2, 4, 5-tetramethylimidazolium side chains based on poly(aryl ether sulfone)s are prepared by aromatic nucleophilic polycondensation, radical substitution and Menshutkin reaction. Their chemical structure and hydrophilic/hydrophobic phase morphology are characterized by hydrogen nuclear magnetic resonance ( 1 H NMR) and atomic force microscope (AFM), respectively. The water uptake, swelling ratio and ionic conductivity for PAES-TMI-x are in the range of 23.8%–48.3%, 8.3%–14.3% and 18.22–96.31 mS/cm, respectively. These AEMs exhibit high alkaline stability, and the ionic conductivity for PAES-TMI-0.25 remains 86.8% after soaking in 2 M NaOH solution at 80 °C for 480 h. The current density of 1205 mA/cm 2 is obtained for the water electrolyzer equipped with PAES-TMI-0.25 in 2 M NaOH solution at 2.0 V and 80 °C, and the electrolyzer also has good operation stability at current density of 500 mA/cm 2 . This work is expected to provide a valuable reference for the selection and design of cations in high-performance AEMs for water electrolysis. Graphical abstract: Image 1 Highlights: Dense 1, 2, 4, 5-tetramethylimidazolium-functionlized AEMs are designed and prepared. A comparative investigation is conducted for the structure and properties of AEMs. The AEMs exhibited high conductivity, good dimensional and alkaline stability. The water electrolysis based on PAES-TMI-0.25 showed high current density.